GESTÃO DAS ORGANIZAÇÕES DE SAÚDE: UM OLHAR SOBRE A AUDITORIA INTERNA DE ENFERMAGEM - Ferrazza, Cristine Aspirot do Couto (2021)
Introduction: The Nursing audit is an essential activity for the economy and quality of care of contemporary hospital institutions. The Brazilian Army’s health organizations have devoted special attention to the qualification of this tool. However, to be efficiently executed, adequate Nursing records in patient charts are fundamental, although the Nursing team does not always understand the relevance of this process. Objective: To analyze the process of managing hospital costs, focusing on the internal audit of Nursing, in a military organization of central Rio Grande do Sul - RS. Methodology: This is a study structured in a mixed approach, conducted in a military hospital of central Rio Grande do Sul - RS and organized in two sequential phases. First, a document analysis of 214 medical records of patients hospitalized between January and April 2020 at the institution analyzed, where scores ranging from 1 to 3 were attributed to the records according to the following requirements: compliance, organization and content, Each medical record can receive a final score between 1 and 9. In a second moment, a Focal Strategic Analysis (In portuguese, Análise Estratégica Focal - AFE) was performed, a methodology elaborated based on the focus group technique and management concepts. Eight professionals participated in this stage, being 4 nurses and 4 nursing technicians. Data collection took place in three meetings, held in the first semester of 2021. Results: In the first quantitative phase, it was observed that the mean score of the analysis of the medical records was 7.31, reflecting weaknesses, mainly in the content of the records. Subsequently, in the qualitative stage of the study, the participants recognized the audit activity, among its potentialities, as a key factor for the qualification of assistance and contribution to organizational financial sustainability. However, the main weaknesses are the lack of technical training of professionals and the lack of knowledge of the nature of the audit activity. In turn, the opportunities and challenges are related to the team’s selection processes, considering the wide turnover of professionals and, often, professional profiles not matching the expected. The strategies outlined by the team include the computerization of the medical records system and, mainly, permanent health education aimed both at auditing activities in Nursing and, in an expanded way, at the health work process. Final Considerations: The audit in Nursing, in the institution, is impaired by failures in records in medical records. The weaknesses relate mainly to the lack of technical training of professionals and the lack of knowledge of the nature of the audit activity. In terms of AFE, the research participants also became agents of transformation of the reality studied, outlining strategies, notably the incorporation of activities of Health Permanent Education (In portuguese, EPS), as a way of transforming the process of work in health.